AquaNet - Chemical parameters from Bolmen AquaNet platform, 2023-04-25–2023-05-31 - Bolmen Research Station (Swedish University of Agricultural Sciences, 2026)
Data contains chemical parameters from grab samples taken from the AquaNet mesocosms.
Bolmen Research Station (2026). AquaNet - Chemical parameters from Bolmen AquaNet platform, 2023-04-25–2023-05-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/ywb77RkciN2Alt88-bQhSsh0
Keywords: SITES AquaNet; Chlorophyll; Fish; Nitrogen Compounds; Phosphorous Compounds; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap